Enhanced Techniques using Dual watermarking for DWT, DCT and SVD - Somra, D.S; Gupta, M (International Journal of Computer Sciences and Engineering, 2019)
Digital image watermarking (DIW)is the way toward embedding watermark into a digital image (DI) for validation and in this way protecting the DI from copyright encroachment. In this paper, a versatile undetectable watermarking plan is paper in dual watermarking process. It is expected that the simplicity with which advanced media can be replicated will prompt an expansion of copyright encroachment. The implement work calculation is depicted in subtle elements. The 2 transform and dual watermarking are useful in course in such an approach to misuse their appealing properties. In this method the wavelet coefficients of the cover image to embed the watermark. The four sub bands of wavelet coefficients can be used to watermark the image. The new DCT coefficients form the singular value decompositions triangular matrices. Then the inverse DCT transform is applied by the inverse DWT. Watermark embedded using this algorithm is highly imperceptible. This scheme is robust against all sorts of attacks. It has very high data hiding capacity.